Cerebral Complications of Snakebite Envenoming: Case Studies - Yu-Kai Huang; Yen-Chia Chen; Chia-Chun Liu; Hui-Chun Cheng; Anthony T. Tu; Kun-Che Chang (Toxins, 2022)
There are an estimated 5.4 million snakebite cases every year. People with snakebite envenoming suffer from severe complications, or even death. Although some review articles cover several topics of snakebite envenoming, a review of the cases regarding cerebral complications, especially rare syndromes, is lacking. Here, we overview 35 cases of snakebite by front-fanged snakes, including Bothrops, Daboia, Cerastes, Deinagkistrodon, Trimeresurus, and Crotalus in the Viperidae family; Bungarus and Naja in the Elapidae family, and Homoroselaps (rare cases) in the Lamprophiidae family. We also review three rare cases of snakebite by rear-fanged snakes, including Oxybelis and Leptodeira in the Colubridae family. In the cases of viper bites, most patients (17/24) were diagnosed with ischemic stroke and intracranial hemorrhage, leading to six deaths. We then discuss the potential underlying molecular mechanisms that cause these complications. In cases of elapid bites, neural, cardiac, and ophthalmic disorders are the main complications. Due to the small amount of venom injection and the inability to deep bite, all the rear-fanged snakebites did not develop any severe complications. To date, antivenom (AV) is the most effective therapy for snakebite envenoming. In the six cases of viper and elapid bites that did not receive AV, three cases (two by viper and one by elapid) resulted in death. This indicates that AV treatment is the key to survival after a venomous snakebite. Lastly, we also discuss several studies of therapeutic agents against snakebite-envenoming-induced complications, which could be potential adjuvants along with AV treatment. This article organizes the diagnosis of hemotoxic and neurotoxic envenoming, which may help ER doctors determine the treatment for unidentified snakebite.